Electronic structure and x-ray magnetic circular dichroism in uranium monochalcogenides - Antonov*, V.N.; Harmon, B.N.; Andryushchenko, O.V.; Bekenev, L.V.; Yaresko, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The electronic structure and x-ray magnetic circular dichroism (XMCD) spectra of US, USe, and UTe are investigated theoretically from first principles, using the fully relativistic Dirac LMTO band structure method. The electronic structure is obtained with the local spin-density approximation (LSDA), as well as with a generalization of the LSDA+U method which takes into account that in the presence of spin–orbit coupling the occupation matrix of localized electrons becomes non-diagonal in spin indexes. The origin of the XMCD spectra in the compounds is examined.